Unmanning : How Humans, Machines and Media Perform Drone Warfare - Chandler, Katherine, 1978- (Book collections on Project MUSE., 2020)
"Unmanning explores the largely understudied development and failure of unmanned aircraft from 1936-1992. Katherine Chandler uses a genealogical approach to explore how contradictions between human, machine, and enemy act politically in the distinct periods of World War II, the Cold War, Vietnam, Israel, and the First Gulf War. The key contributions that Unmanning makes to the field of critical military studies are to problematize what drones and unmanned aircraft are through an analysis of history, to demonstrate how networked actions between human and nonhuman that comprise unmanned aircraft operate through duplicity, and to examine the failures central to the development, experimental use, and deployment of drones that are at once technological, social, and political."--